Midostaurin, bortezomib and MEC in relapsed/refractory acute myeloid leukemia. Issue 9 (1st September 2016) - Walker, Alison R.; Wang, Hongyan; Walsh, Katherine; Bhatnagar, Bhavana; Vasu, Sumithira; Garzon, Ramiro; Canning, Renee; Geyer, Susan; Wu, Yue-Zhong; Devine, Steven M.; Klisovic, Rebecca; Blum, William; et al.
Abstract: Targeting aberrant tyrosine kinase activity may impact clinical outcome in acute myeloid leukemia (AML). We conducted a phase I study of the tyrosine kinase inhibitor midostaurin with bortezomib alone and in combination with chemotherapy in patients with AML. Patients on dose levels 1 and 2 (DL1 & 2) received midostaurin 50 mg bid and escalating doses of bortezomib (1 to 1.3 mg/m2). Patients on DL3 or higher received midostaurin and bortezomib following chemotherapy with mitoxantrone, etoposide, cytarabine (MEC). None of the patients enrolled to DL1 & 2 had dose-limiting toxicities (DLTs) or a clinical response. Among patients enrolled to DL3 or higher, DLTs were peripheral neuropathy, decrease in ejection fraction and diarrhea. A 56.5% CR rate and 82.5% overall response rate (CR + CR with incomplete neutrophil or platelet count recovery) were observed. The midostaurin/bortezomib/MEC combination is active in refractory/relapsed AML, but is associated with expected drug-related toxicities (NCT01174888).